RANCANG BANGUN SISTEM INFORMASI REKAM MEDIS BERBASIS WEB (STUDI KASUS: PUSKESMAS TAMBARANGAN) - Salasiah Salasiah; Afrinal Afrinal (Program Studi Teknik Informatika, Politeknik Hasnur, 2021)
The Puskesmas is a functional health organization which is the center for community health development and fostering community participation. Existing services at the puskesmas must be carried out properly and correctly in order to simplify and speed up the flow of services, a medical record data processing information system is very appropriate to simplify existing services at the puskesmas. This study aims to produce a patient medical record information system at Tambarangan Public Health Center. This system is built on a web-based basis using the CodeIgniter framework and will be developed using the waterfall medote.